Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's solve the given system of linear equations step-by-step.
Given equations:
[tex]\[ 15x + 7y = 10 \tag{1} \][/tex]
[tex]\[ 8x + 6y = -6 \tag{2} \][/tex]
Part 1: Write the system of equations in [tex]\( AX = B \)[/tex] form
In matrix notation, we can represent the system as follows:
[tex]\[ A = \begin{pmatrix} 15 & 7 \\ 8 & 6 \end{pmatrix}, \quad X = \begin{pmatrix} x \\ y \end{pmatrix}, \quad B = \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
So the equation [tex]\( AX = B \)[/tex] can be written as:
[tex]\[ \begin{pmatrix} 15 & 7 \\ 8 & 6 \end{pmatrix} \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
Part 2: Find [tex]\( A^{-1} \)[/tex]
The inverse of a 2x2 matrix [tex]\( A = \begin{pmatrix} a & b \\ c & d \end{pmatrix} \)[/tex] is given by:
[tex]\[ A^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For our matrix [tex]\( A \)[/tex]:
[tex]\[ A = \begin{pmatrix} 15 & 7 \\ 8 & 6 \end{pmatrix} \][/tex]
We calculate the determinant [tex]\( \text{det}(A) \)[/tex]:
[tex]\[ \text{det}(A) = 15 \cdot 6 - 7 \cdot 8 = 90 - 56 = 34 \][/tex]
Thus, the inverse [tex]\( A^{-1} \)[/tex] is:
[tex]\[ A^{-1} = \frac{1}{34} \begin{pmatrix} 6 & -7 \\ -8 & 15 \end{pmatrix} \][/tex]
Simplifying, we get:
[tex]\[ A^{-1} = \begin{pmatrix} \frac{6}{34} & \frac{-7}{34} \\ \frac{-8}{34} & \frac{15}{34} \end{pmatrix} = \begin{pmatrix} \frac{3}{17} & \frac{-7}{34} \\ \frac{-4}{17} & \frac{15}{34} \end{pmatrix} \][/tex]
Part 3: Solve the system using the matrix equation
To find [tex]\( X \)[/tex] from [tex]\( AX = B \)[/tex], we use the formula [tex]\( X = A^{-1}B \)[/tex].
Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( B \)[/tex]:
[tex]\[ A^{-1} = \begin{pmatrix} \frac{3}{17} & \frac{-7}{34} \\ \frac{-4}{17} & \frac{15}{34} \end{pmatrix} , \quad B = \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
[tex]\[ X = \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} \frac{3}{17} & \frac{-7}{34} \\ \frac{-4}{17} & \frac{15}{34} \end{pmatrix} \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
Calculating the product:
[tex]\[ x = \frac{3}{17} \cdot 10 + \frac{-7}{34} \cdot (-6) = \frac{30}{17} + \frac{42}{34} = \frac{30}{17} + \frac{21}{17} = \frac{51}{17} = 3 \][/tex]
[tex]\[ y = \frac{-4}{17} \cdot 10 + \frac{15}{34} \cdot (-6) = \frac{-40}{17} + \frac{-90}{34} = \frac{-40}{17} + \frac{-45}{17} = \frac{-85}{17} = -5 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (3, -5) \][/tex]
Given equations:
[tex]\[ 15x + 7y = 10 \tag{1} \][/tex]
[tex]\[ 8x + 6y = -6 \tag{2} \][/tex]
Part 1: Write the system of equations in [tex]\( AX = B \)[/tex] form
In matrix notation, we can represent the system as follows:
[tex]\[ A = \begin{pmatrix} 15 & 7 \\ 8 & 6 \end{pmatrix}, \quad X = \begin{pmatrix} x \\ y \end{pmatrix}, \quad B = \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
So the equation [tex]\( AX = B \)[/tex] can be written as:
[tex]\[ \begin{pmatrix} 15 & 7 \\ 8 & 6 \end{pmatrix} \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
Part 2: Find [tex]\( A^{-1} \)[/tex]
The inverse of a 2x2 matrix [tex]\( A = \begin{pmatrix} a & b \\ c & d \end{pmatrix} \)[/tex] is given by:
[tex]\[ A^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For our matrix [tex]\( A \)[/tex]:
[tex]\[ A = \begin{pmatrix} 15 & 7 \\ 8 & 6 \end{pmatrix} \][/tex]
We calculate the determinant [tex]\( \text{det}(A) \)[/tex]:
[tex]\[ \text{det}(A) = 15 \cdot 6 - 7 \cdot 8 = 90 - 56 = 34 \][/tex]
Thus, the inverse [tex]\( A^{-1} \)[/tex] is:
[tex]\[ A^{-1} = \frac{1}{34} \begin{pmatrix} 6 & -7 \\ -8 & 15 \end{pmatrix} \][/tex]
Simplifying, we get:
[tex]\[ A^{-1} = \begin{pmatrix} \frac{6}{34} & \frac{-7}{34} \\ \frac{-8}{34} & \frac{15}{34} \end{pmatrix} = \begin{pmatrix} \frac{3}{17} & \frac{-7}{34} \\ \frac{-4}{17} & \frac{15}{34} \end{pmatrix} \][/tex]
Part 3: Solve the system using the matrix equation
To find [tex]\( X \)[/tex] from [tex]\( AX = B \)[/tex], we use the formula [tex]\( X = A^{-1}B \)[/tex].
Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( B \)[/tex]:
[tex]\[ A^{-1} = \begin{pmatrix} \frac{3}{17} & \frac{-7}{34} \\ \frac{-4}{17} & \frac{15}{34} \end{pmatrix} , \quad B = \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
[tex]\[ X = \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} \frac{3}{17} & \frac{-7}{34} \\ \frac{-4}{17} & \frac{15}{34} \end{pmatrix} \begin{pmatrix} 10 \\ -6 \end{pmatrix} \][/tex]
Calculating the product:
[tex]\[ x = \frac{3}{17} \cdot 10 + \frac{-7}{34} \cdot (-6) = \frac{30}{17} + \frac{42}{34} = \frac{30}{17} + \frac{21}{17} = \frac{51}{17} = 3 \][/tex]
[tex]\[ y = \frac{-4}{17} \cdot 10 + \frac{15}{34} \cdot (-6) = \frac{-40}{17} + \frac{-90}{34} = \frac{-40}{17} + \frac{-45}{17} = \frac{-85}{17} = -5 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (3, -5) \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.